Simplify The following equations(This is algebra, so PLEASE, only answer if you KNOW FOR SURE, thank you)

3a+7b+2c-a-4b

-8a-b-(-6c)-2a-b-5c

b-4c+3a-c-9b-4a

Answers

Answer 1
Answer: mostly collect like terms
use associative property which is
(a+b)+c=a+(b+c)
also -a+b-c=(-a)+(b)+(-c) so you can move them around
and remember that:
you just use a general rule
x+x=2x
x^2+x^2=2x^2
3xy4xy=7xy
3x+4x^2=3x+4x^2
youcan only add like terms( like terms are terms that are same name like xor y are differnt, and like terms have same power exg x^2 and x^3 andx^1/2 and such

I will oly put the naswers because I don't have much time

first one: 2a+3b+2c

second one: remember that -(-6c)=+6c so the answer is c-10a-2b

third one: -a-8b-5c


Related Questions

What is the decimal form of 100/3, 100/5, and100 /6?
A bicycle store costs $1650 per month to operate.The store pays an average of $60 per bike.The average selling price of each bicycle is $90 how many bicycles must the store sell each month to break even
What is -2x-7=3(4x+7)
A car wash detailed 288 cars in 9 hours. At what rate did the car wash detail cars in cars per hour? A. 31 cars per hour B. 33 cars per hour C. 30 cars per hour D. 32 cars per hour
The fraction 8/9 is equivalent to what percent round your percent to the nearest tenth

Would anyone be willing to help me with geometry?

Answers

From the second and third steps, we know that m∠TUV = m∠1 + m∠2. We also know that m∠XWV = m∠3 + m∠4. Since ∠TUV and ∠XMV both measure 90°, we can set their measures equal to each other:

m∠TUV = m∠XMV

or equivalently:

m∠1 + m∠2 = m∠3 + m∠4

Next, we can use the fact that ∠1 ≅ ∠3 to say that m∠1 = m∠3, while allows us to replace one with the other. Here, we'll replace m∠3 with m∠1:

m∠1 + m∠2 = m∠1 + m∠4

Subtracting m∠1 from either side:

m∠2 = m∠4, which implies that ∠2 ≅ ∠4, as we wanted to show.

The legs of a right triangle measure 6 inches and 12 inches what is the area fo the triangle

Answers

Answer: 36

Step-by-step explanation:

The area of a triangle is (1/2)lw <- that just means that a triangle is half a square. Length * width is the original formula for solving the area of a square.

6 * 12 = 72; 72/2 = 36

36 because the triangle formula is half of base times height. Base times height would be 72 so half of that is 36

On a coordinate plane, a solid straight line has a positive slope and goes through (0, negative 1) and (3, 0). Everything above and to the left of the line is shaded.Which linear inequality is represented by the graph?

y ≤ One-thirdx − 1
y ≥ One-thirdx − 1
y < 3x − 1
y > 3x − 1

Answers

Answer:

Option B.

Step-by-step explanation:

A solid straight line passes through (0, -1) and (3, 0)

Slope of the line = (y-y')/(x-x')

= (0+1)/(3-0)

= (1)/(3)

Equation of the line passing through (0, -1) will be  

y - y' = m(x - x')

y+1=(1)/(3)(x-0)

y=(1)/(3)x-1

Since this line is solid then there will the sign of (≥ or ≤)

If everything above and to the left of the line is shaded then the inequality will be

y\geq (1)/(3)x-1

Therefore, the answer will be option B. y\geq (1)/(3)x-1

Answer: C

Step-by-step explanation:

Just took the test and made a 100%

Triangle XYZ is reflected across the line mc013-1.jpg, and X’ = (2, –15). What are the coordinates of X?

Answers

The image is not provided, therefore for your understanding, I will assume that the image has been reflected across y-axis (condition taken from a similar question).
There are certain reflection rules across whatever you want to reflect. In this case, we want to reflect the shape across the y-axis.
When you reflect a point across the y-axis, y coordinate remains the same, but the x-coordinate is transformed into its opposite, means the sign of the x coordinate will be changed from positive to negative or negative to positive.
Thus,
(x , y)→(-x , y)

X’ = (2, –15) is the point given to you, which is the reflected point. To find the pre-image, consider the rule described above.

X’ = (2, –15) → X = (-2 , -15)

In case, the question says it is reflected over x-axis then we would use another rule which says When you reflect a point across the x-axis, the x-coordinate remains the same, but  y-coordinate is transformed into its opposite, means the sign of the x coordinate will be changed from positive to negative or negative to positive.
Then,
X’ = (2, –15) → X = (2 , 15)

Answer:

x-2

Step-by-step explanation:

photomath app

What is 3-3 x 6+2=?????????????????????????????????

Answers

-13 is what I came up with, and believe me, it is what the answer is
 3-3 x 6+2= -13
The answer= -13

A juice can is about 2.25 inches in diameter what is the circumference

Answers

about 7.07 inches. to get this do 2.25 x 3.14 (pi) to get about 7.07

Final answer:

The circumference of a juice can with a diameter of 2.25 inches is approximately 7.065 inches.

Explanation:

The circumference of a circle can be found using the formula C = πd, where C is the circumference and d is the diameter. In this case, the diameter of the juice can is given as 2.25 inches. Therefore, the circumference can be calculated as C = 3.14 * 2.25 = 7.065 inches. So, the circumference of the juice can is approximately 7.065 inches.

Learn more about circumference of a circle here:

brainly.com/question/26605972

#SPJ5